Development of problem based learning with peer assessment model to enhance creative thinking and piano skills for non-piano college students - Yang, Liheng; Ratanaolarn, Thanin; Petsangsri, Sirirat; Cui, Jianming (Edelweiss Applied Science and Technology, 2026)
This study aimed to develop a Problem-Based Learning (PBL) model integrated with peer assessment to enhance creative thinking and piano skills among non-piano college students. The study employed a research and development approach combined with a quasi-experimental design to evaluate the effectiveness of the developed instructional model. The participants consisted of 40 second-year non-piano major students from a university in Yuncheng City, China, who were divided into an experimental group (n = 20) and a control group (n = 20). The experimental group was taught using the PBL with peer assessment model, while the control group received traditional piano instruction. The intervention lasted for eight weeks. Data were collected through piano performance assessments and a creative thinking questionnaire, and analyzed using multivariate analysis of variance (MANOVA) and independent samples t-tests. The results indicated that students in the experimental group demonstrated significantly higher scores in both piano skills and creative thinking compared with the control group (p < .001). The experimental group achieved higher mean scores in rhythm and timing (M = 23) and style and mood (M = 8), compared with the control group (M = 18 and M = 6, respectively). Creative thinking scores increased to a mean of 4.46 in the experimental group, while the control group scored 2.97. These findings suggest that the developed PBL with peer assessment model effectively improves musical performance and creative thinking. Future research should examine the long-term impact of the model and explore its applicability in other music education contexts.